2021
DOI: 10.21037/atm-20-4707
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of GMP-grade human iPSC-derived retinal pigment epithelial cells in rodent model: the first pre-clinical study for safety and efficacy in China

Abstract: Background: Age-related macular degeneration (AMD) is the leading cause of blindness in the elderly due in large part to age-dependent atrophy of retinal pigment epithelium (RPE) cells. RPE cells form a monolayer located between the choroid and the outer segments of photoreceptors, playing multifarious roles in maintenance of visual function. Allogeneically induced pluripotent stem cell-derived RPE (iPSC-RPE or iRPE) has become a potential approach for providing an abundant source of donors for clinical cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Tremendous work has been done to seek therapeutic breakthroughs in hereditary retinal diseases ( Chen et al, 2013 ; Mandai et al, 2017 ; Echigoya et al, 2018 ; Jin et al, 2019 ; Pendse et al, 2019 ; Zhang et al, 2021 ; Zhao et al, 2021 ). Significant progress has been achieved in research on cell replacement therapy, AON-based gene therapy, gene editing, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Tremendous work has been done to seek therapeutic breakthroughs in hereditary retinal diseases ( Chen et al, 2013 ; Mandai et al, 2017 ; Echigoya et al, 2018 ; Jin et al, 2019 ; Pendse et al, 2019 ; Zhang et al, 2021 ; Zhao et al, 2021 ). Significant progress has been achieved in research on cell replacement therapy, AON-based gene therapy, gene editing, etc.…”
Section: Discussionmentioning
confidence: 99%
“…A long-term preclinical safety study reported no tumor formation or abnormal proliferation after subretinal injection of iPSC-RPE cells in immunodeficient mice until 15 weeks post surgery. In addition, transplanted hiPSC-RPE cells survived and rescued the visual function for at least 15 weeks post surgery under immunosuppressive conditions in the retinal dystrophic rat model [ 168 ]. In a clinical study, where an iPSC-RPE graft sheet, derived from the patient’s skin fibroblasts, was transplanted for the treatment of AMD, no serious complications were reported and no unexpected proliferation or sign of local or systemic malignant disease was observed.…”
Section: Stem Cells For Replacement Of the Retinal Pigment Epitheliummentioning
confidence: 99%
“…While significant strides have been made in hPSC differentiation, there remain challenges in the differentiation processes of hESCs and iPSCs, ultimately limiting the widespread use of stem cell technology in research programs and cell replacement therapies. The current state-of-the-art method to induce lineage differentiation from hPSCs involves controlling the differentiation process via the stepwise sequential addition of growth factors and cytokines (Table 1), which are known to play a role during certain steps of differentiation and ultimately induce the phenotypic characteristics ( [41][42][43] Although this has enabled the generation of various cell types, including cells with features of neural subpopulations (cholinergic and dopaminergic neurons), cardiac muscle cells, and hepatocytes, these cells resemble fetal tissue more than adult tissue, in most cases [16]. The use of incomplete differentiated progeny from PSC may hold risks associated with tumorigenicity and excessive proliferation.…”
Section: Differentiation Of Hpscs To Clinically Relevant Phenotypic Cellsmentioning
confidence: 99%